The Effect of Compensation and Work Motivation on the Performance of Surabaya Hebat Cadres in Sidodadi Sub-district with Work Discipline as a Mediating Variable - Edy Purnama, Dwi Sapta; Burhanudin, Burhanudin; Yulianti, Emma (Universitas Muhammadiyah Pontianak, 2025)
This study analyzes the influence of compensation and work motivation on the performance of Surabaya Hebat cadres in Sidodadi Sub-district with work discipline as a mediating variable. Using a quantitative approach with a survey method and PLS-SEM analysis on cadre respondents, results demonstrate that compensation and motivation have both direct and indirect positive effects through discipline. The findings highlight the importance of designing fair incentive systems, motivation enhancement programs, and discipline-building strategies to improve the effectiveness, accountability, and sustainability of community health services while supporting local government efforts to strengthen health promotion at the urban community level.